Preparation method of hydrogel reinforced cement-based wave-absorbing material
By introducing the combination of molybdenum carbide/seaweed carbon powder and polyvinyl alcohol hydrogel into cement-based absorbing materials, the network structure is formed, which solves the narrow absorption frequency band, low peak value and insufficient mechanical properties of traditional cement-based absorbing materials. The problem of efficient electromagnetic wave absorption and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202411537892.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional cement-based absorbent materials have problems such as single loss mechanism of absorbent, narrow absorption frequency band, low peak value, uneven dispersion, deterioration of mechanical properties, reduced electromagnetic wave attenuation capability, expensive construction and complex process.
Use hydrogel-enhanced cement-based absorbing material, in which the wave-permeable layer consists of silicate cement, fly ash, water reducer, gas induction agent and dolomite stone material. The intermediate layer uses molybdenum carbide/seaweed carbon powder and polymerization The vinyl alcohol hydrogel is combined to form a mesh structure with excellent conductivity and mechanical properties.
It improves the electromagnetic wave absorption capacity and mechanical properties of the material, solves the problems of narrow absorption frequency band and low peak value, reduces costs, simplifies the process, and improves the compressive, split tensile strength and early crack resistance of the material.
Smart Images

Figure CN119408245A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of wave absorbing materials, and in particular relates to a hydrogel-reinforced cement-based wave absorbing material and a preparation method thereof. Background Art The rapid development of 5G technology and the widespread use of portable electronic devices such as smartphones and tablets have brought great convenience to people, but have inevitably caused a large amount of electromagnetic pollution, posing a threat to human health and the performance of electronic equipment.
[0002] Cement-based absorbing material is a new type of material that fills absorbent into cement to attenuate electromagnetic waves and reduce secondary pollution of electromagnetic waves. However, traditional cement-based absorbing materials usually have the following disadvantages: 1. The absorbent loss mechanism is single, resulting in defects such as narrow absorption band and low peak value; 2. Uneven dispersion of absorbent leads to deterioration of cement mechanical properties and reduced electromagnetic wave attenuation capacity; 3. Disadvantages such as high cost and complex process have hindered the development of cement-based absorbing materials. Summary of the invention
[0003] In view of the problems existing in the existing cement-based absorbing materials, the present invention provides a hydrogel-reinforced cement-based absorbing material and a preparation method thereof.
[0004] The hydrogel-reinforced cement-based absorbing material is characterized in that the upper and lower layers of the absorbing material are made of wave-transparent layers, and the middle layer is made of absorbing hydrogel, wherein: The wave-transmitting layer is composed of silicate cement, fly ash, water reducing agent, air entraining agent, and dolomite material, wherein: silicate cement 260-300 kg / m 3 , fly ash 80~100 kg / m 3 , water reducing agent 2~3 kg / m 3 , air entraining agent 0.08~0.16 kg / m 3 , water 110~140 kg / m 3 , dolomite material 1965~2267 kg / m 3 .
[0005] The wave-absorbing hydrogel is composed of molybdenum carbide / seaweed carbon powder, defoamer, sodium alginate, polyvinyl alcohol, and water, wherein: molybdenum carbide / seaweed carbon powder 2.4-3.6 kg / m 3 , defoamer 0.5~0.6 kg / m 3 , sodium alginate 0.6~0.7 kg / m 3 , polyvinyl alcohol 30~42 kg / m 3 , water 66.4~76.4 kg / m 3 .
[0006] Preferably, the cement is P·MH32.5 grade medium heat Portland cement with a fineness of less than 80 μm and a specific surface area of ≥370 kg / m 3 .
[0007] Preferably, the fly ash is Class F, Grade I fly ash, with a fineness of <80 μm.
[0008] Preferably, the water reducer is a polycarboxylic acid high-efficiency water reducer with a solid content of ≥8.5%; the defoamer is an organosilicon defoamer with a viscosity of 160-200 MPa·s.
[0009] Preferably, the dolomite material includes coarse aggregate and fine aggregate, wherein: coarse aggregate 1225~1413 kg / m 3 , fine aggregate 740~854 kg / m 3 .
[0010] Preferably, the molybdenum carbide / seaweed carbon powder has a particle size of 120-180 μm and a specific surface area of ≥250 m 3 / g; wherein the particle size of molybdenum carbide particles is 50-80nm.
[0011] The preparation method of the hydrogel-reinforced cement-based absorbing material is characterized by comprising the following steps: S1, the seaweed was washed three times with acetone, ethanol and pure water, and then dried in an oven for 12 h. The dried seaweed was made into seaweed powder. The seaweed powder and potassium hydroxide were dissolved in water at a mass ratio of 1:2, stirred for 5-8 h to mix evenly, and then dried in an oven at 100-110 °C. After the dried sample was fully ground, it was heated in a N2 environment at a heating rate of 2-3 °C / min. After heating to 600-800 °C, it was activated and pyrolyzed for 2-3 h. 1 mol / L hydrochloric acid was added dropwise to the product until the pH was 7±0.5, and then the seaweed carbon was obtained after centrifugal washing and drying.
[0012] S2, take 10kg / m 3 Molybdic acid, 110kg / m 3 Polyvinylpyrrolidone (PVP) is dissolved in 270kg / m 3 Stir in methanol for 2-3h, then add 12kg / m 3 The seaweed carbon prepared in step S1 is stirred for 1-2 hours and then ultrasonicated for 30-60 minutes to make it uniformly dispersed, and the mixed solution is placed in a 100-110°C oven and dried for 24 hours. The dried black powder is placed in a tube furnace and calcined at 800-1000°C for 2-3 hours to obtain molybdenum carbide / seaweed carbon powder.
[0013] S3, 30~42 kg / m3 Polyvinyl alcohol is dissolved in 66.4kg / m 3 In water, 0.6~0.7kg / m 3 Sodium alginate dissolved in 10kg / m 3 Heat the water to 80~90℃ and add 0.5~0.6kg / m 3 Defoaming agent, 2.4~3.6kg / m 3 The molybdenum carbide / seaweed carbon powder prepared in step S2 is mixed and stirred for 50-70 seconds, and sodium hydroxide solution is added dropwise until the pH is greater than 12. After the solution is cooled, it is poured into a steel mold for curing to a thickness of 1-6 mm. After demolding, it is freeze-thawed at -20°C for 3-15 times to obtain a microwave absorbing hydrogel.
[0014] S4, 1965~2267 kg / m 3 Dolomite, 260~300 kg / m 3 Portland cement and 80~100 kg / m 3 Add fly ash into the mixer and stir evenly for 60 to 80 seconds to obtain wave-transmitting layer powder.
[0015] S5, add 2~3 kg / m 3 , air entraining agent 0.08~0.16 kg / m 3 110~140 kg / m 3 The water is mixed evenly to obtain a wave-transmitting layer mixed liquid.
[0016] S6, start the stirrer, slowly add the mixed solution prepared in step S5 into the wave-transmitting layer powder prepared in step S4 within 15 seconds, and stir slowly for 35 to 60 seconds to obtain a wave-transmitting layer mixed slurry.
[0017] S7, pour the wave-transmitting layer mixed slurry prepared in step S6 into a 300mm×300mm×60mm steel mold and cast 24~27mm, let it stand for 5~30min, then place the absorbing hydrogel on the wave-transmitting layer mixed slurry, then cast the remaining wave-transmitting layer mixed slurry, and cure for 24h to form it. After demolding, cure it in a curing room for 28 days to obtain a hydrogel reinforced cement-based absorbing material.
[0018] The technical principle of the present invention is as follows: cement, fly ash and coarse aggregate are used as skeleton materials of the electromagnetic wave transparent layer to improve the strength of concrete while allowing a large amount of electromagnetic waves to penetrate the material; molybdenum carbide / seaweed carbon powder and hydrogel composition are used as the electromagnetic wave absorption layer, and seaweed carbon and molybdenum carbide are compounded to form a molybdenum carbide-carbon interface, thereby generating a large amount of interface polarization, thereby enhancing the loss of electromagnetic waves inside the material; the rich pore structure and high specific surface area of seaweed carbon increase the electromagnetic wave transmission path, further enhancing the electromagnetic wave attenuation ability; hydrogel is not only conducive to the dispersion of absorbing materials, but also reduces the clustering effect of molybdenum carbide / seaweed carbon powder, and after drying, it can form a mesh structure with excellent conductivity and mechanical properties, thereby synergistically enhancing the toughness and absorbing ability of concrete.
[0019] Compared with the existing methods, the significant advantages of the present invention are: 1. The present invention uses molybdenum carbide / seaweed carbon powder composite material as absorbent. Its raw material seaweed has a wide source, simple preparation process and low cost, which is conducive to solving the problem of seaweed pollution. The prepared composite material belongs to a dual dielectric material, which can effectively solve the defects of narrow absorption band and low peak value caused by the single absorbent loss mechanism.
[0020] 2. Polyvinyl alcohol hydrogel with high strength and high toughness is used as the early anti-cracking reinforcement material of concrete. In the electromagnetic wave absorption layer, polyvinyl alcohol hydrogel is not only conducive to the dispersion of the absorber and reduces the clustering effect of the absorber, but also forms a high-molecular conductive and high-toughness cross-linked network after drying to further enhance the concrete's wave absorption and anti-cracking properties.
[0021] 3. Different from traditional absorbing materials, the hydrogel-reinforced cement-based absorbing material prepared by the present invention has the advantages of good mechanical properties and high absorption strength, and has a significant attenuation effect on 2-18 GHz high-frequency electromagnetic waves. Its minimum reflection loss can reach -29.6 dB, and the effective bandwidth less than -10 dB is 6 GHz. Its 28d compressive strength can reach 31.8 MPa, and its splitting tensile strength can reach 3.91 MPa, which meets the needs of general industrial and civil building materials and can be used as building absorbing materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of molybdenum carbide and seaweed carbon composite material.
[0023] Figure 2 This is a TEM image of molybdenum carbide and seaweed carbon composite material.
[0024] Figure 3 This is the XRD diagram of molybdenum carbide and seaweed carbon composite material. The horizontal axis is the scanning angle, the scanning angle range is 20 degrees to 90 degrees, and the vertical axis is the intensity.
[0025] Figure 4This is a test of the early crack resistance of the hydrogel-reinforced cement-based absorbing material obtained in Example 8.
[0026] Figure 5 This is a diagram of the wave absorbing performance of the hydrogel-enhanced cement-based wave absorbing material obtained in Example 8, where the horizontal axis is the frequency, the vertical axis is the reflection loss value, and the dotted line is the effective frequency.
[0027] Figure 6 It is a cross-sectional schematic diagram of a hydrogel-reinforced cement-based absorbing material. DETAILED DESCRIPTION
[0028] In order to verify the high absorption performance, high toughness and other effects of the hydrogel-reinforced cement-based absorbing material designed by the present invention, it is further described below in combination with specific implementation methods. In the absence of conflict, the embodiments of the present invention and their features can be combined with each other.
[0029] In the following embodiments, in order to make the concrete have certain wave absorbing performance, the present invention conducts in-depth research on the wave absorbing material, and finally selects molybdenum carbide / seaweed carbon powder material as the wave absorbing agent.
[0030] In the following examples, the cement used is P·MH32.5 grade medium heat Portland cement with a fineness of 55 μm and a specific surface area of 410 kg / m 3 ; In the following examples, the coarse aggregate used is dolomite crushed stone, and the saturated surface dry apparent density of the aggregate is 2700 kg / m 3 , bulk density 1580kg / m 3 ; In the following examples, the fly ash used is Class F Grade I fly ash with a fineness of 65 μm; In the following examples, the sodium hydroxide, sodium alginate, ammonium molybdate, polyvinyl pyrrolidone, and polyvinyl alcohol used are commercially available chemical agents; the degree of alcoholysis of polyvinyl alcohol is 99% and the viscosity is 3.8 MPa·s; In the following examples, the water reducer used is a polycarboxylic acid high-efficiency water reducer with a solid content of 9.5%; the defoamer is an organosilicon defoamer with a viscosity of 190 MPa·s.
[0031] In the following examples, the water used was laboratory living water.
[0032] In the following examples, the bow method is used to test the wave absorption performance (2-18 GHz) of the material, which is obtained by testing with an Agilent P5004A vector network analyzer.
[0033] Example 1: In this example, the hydrogel-reinforced cement-based absorbing material has a wave-transmitting layer in the upper and lower layers and a wave-absorbing hydrogel in the middle layer. The ratio of the raw materials of the wave-transmitting layer (kg / m 3) is: Portland cement 255, fly ash 63, dolomite coarse aggregate 1225, dolomite fine aggregate 740, high-efficiency water reducer 2.2, air entraining agent 0.04, water 134. The raw material ratio of the wave-absorbing hydrogel (kg / m 3 ) is 2.4 molybdenum carbide / seaweed carbon powder and 30 polyvinyl alcohol.
[0034] The seaweed was washed three times with acetone, ethanol and pure water, and then dried in an oven for 12 hours. The dried seaweed was powdered, and the powder was dissolved in water with potassium hydroxide at a mass ratio of 1:2. After stirring for 6 hours, it was dried in an oven at 110°C, and then heated to 700°C in a tube furnace and pyrolyzed for 3 hours. 1 mol / L hydrochloric acid was added to the product until the pH was about 7, and seaweed carbon was obtained after drying. Take 12kg / m 3 Seaweed carbon, 10kg / m 3 Molybdic acid, 110kg / m 3 Polyvinylpyrrolidone (PVP) is dissolved in 270kg / m 3 After stirring in methanol for 3 h, the mixed solution was placed in a 110°C oven and dried for 24 h. It was then placed in a tube furnace and calcined at 900°C for 3 h to obtain molybdenum carbide / seaweed carbon powder. 3 Polyvinyl alcohol powder dissolved in 66kg / m 3 In water, 0.6kg / m 3 Sodium alginate is dissolved in 16.5kg / m 3 Heat the water to 85°C and add 0.5kg / m 3 Defoamer, 2.4kg / m 3 Molybdenum carbide / seaweed carbon powder was mixed and stirred for 65 seconds, and sodium hydroxide solution was added until the pH was > 12. After the solution was cooled, it was poured into a 300mm×300mm×6mm steel mold for curing. After demoulding, it was freeze-thawed for 3 times at -20℃ to obtain the wave-absorbing hydrogel. 3 、P·MH32.5 grade medium heat Portland cement 260kg / m 3 、Class I fly ash 63kg / m 3 , fine aggregate 740kg / m 3 , and add them into the mixer in sequence, stir evenly for 65 seconds to obtain mixture B. Add 2.2kg / m 3 , air entraining agent 0.04 kg / m 3 Mixing water 134 kg / m 3Evenly mix to obtain solution C. Slowly add solution C to mixture B within 15 seconds, slowly mix and stir for 50 seconds, pour the mixed slurry into a 300mm×300mm×60mm steel mold and pour 27mm, let it stand for 5 minutes, place the prepared absorbing hydrogel on the slurry, pour the remaining slurry, cure for 24 hours to form, and cure in a curing room for 28 days after demolding.
[0035] Example 2: The hydrogel-reinforced cement-based absorbing material of this example, the absorbing material has a wave-transmitting layer in the upper and lower layers, and a wave-absorbing hydrogel in the middle layer. The ratio of the raw materials of the wave-transmitting layer (kg / m 3 ) is: Portland cement 255, fly ash 63, dolomite coarse aggregate 1225, dolomite fine aggregate 740, high-efficiency water reducer 2.2, air entraining agent 0.04, water 134. The raw material ratio of the wave-absorbing hydrogel (kg / m 3 ) is molybdenum carbide / seaweed carbon powder 3.0, polyvinyl alcohol 30.
[0036] The seaweed was washed three times with acetone, ethanol and pure water, and then dried in an oven for 12 hours. The dried seaweed was powdered, and the powder was dissolved in water with potassium hydroxide at a mass ratio of 1:2. After stirring for 6 hours, it was dried in an oven at 110°C, and then heated to 700°C in a tube furnace and pyrolyzed for 3 hours. 1 mol / L hydrochloric acid was added to the product until the pH was about 7, and seaweed carbon was obtained after drying. Take 12kg / m 3 Seaweed carbon, 10kg / m 3 Molybdic acid, 110kg / m 3 Polyvinylpyrrolidone (PVP) is dissolved in 270kg / m 3 After stirring in methanol for 3 h, the mixed solution was placed in a 110°C oven and dried for 24 h. It was then placed in a tube furnace and calcined at 900°C for 3 h to obtain molybdenum carbide / seaweed carbon powder. 3 Polyvinyl alcohol powder dissolved in 66kg / m 3 In water, 0.6kg / m 3 Sodium alginate is dissolved in 16.5kg / m 3 Heat the water to 85°C and add 0.5kg / m 3 Defoamer, 3kg / m 3 Molybdenum carbide / seaweed carbon powder was mixed and stirred for 65 seconds, and sodium hydroxide solution was added until the pH was > 12. After the solution was cooled, it was poured into a 300mm×300mm×6mm steel mold for curing. After demoulding, it was freeze-thawed for 3 times at -20℃ to obtain the wave-absorbing hydrogel. 3 、P·MH32.5 grade medium heat Portland cement 260kg / m 3 、Class I fly ash 63kg / m 3 , fine aggregate 740kg / m 3, and add them into the mixer in sequence, stir evenly for 65 seconds to obtain mixture B. Add 2.2kg / m 3 , air entraining agent 0.04 kg / m 3 Mixing water 134 kg / m 3 Evenly mix to obtain solution C. Slowly add solution C to mixture B within 15 seconds, slowly mix and stir for 50 seconds, pour the mixed slurry into a 300mm×300mm×60mm steel mold, pour 18mm, let it stand for 5 minutes, place the prepared absorbing hydrogel on the slurry, repeat twice, pour the remaining slurry, cure for 24 hours to form, and cure in a curing room for 28 days after demolding.
[0037] Example 3: The hydrogel-reinforced cement-based absorbing material of this example, the upper and lower layers of the absorbing material are made of transparent layers, and the middle layer is made of absorbing hydrogel. The raw material ratio of the transparent layer (kg / m 3 ) is: Portland cement 255, fly ash 63, dolomite coarse aggregate 1225, dolomite fine aggregate 740, high-efficiency water reducer 2.2, air entraining agent 0.04, water 134. The raw material ratio of the wave-absorbing hydrogel (kg / m 3 ) is 3.6 molybdenum carbide / seaweed carbon powder and 42 polyvinyl alcohol.
[0038] The seaweed was washed three times with acetone, ethanol and pure water, and then dried in an oven for 12 hours. The dried seaweed was powdered, and the powder was dissolved in water with potassium hydroxide at a mass ratio of 1:2. After stirring for 6 hours, it was dried in an oven at 110°C, and then heated to 700°C in a tube furnace and pyrolyzed for 3 hours. 1 mol / L hydrochloric acid was added to the product until the pH was about 7, and seaweed carbon was obtained after drying. Take 12kg / m 3 Seaweed carbon, 10kg / m 3 Molybdic acid, 110kg / m 3 Polyvinylpyrrolidone (PVP) is dissolved in 270kg / m 3 After stirring in methanol for 3 h, the mixed solution was placed in a 110°C oven and dried for 24 h. It was then placed in a tube furnace and calcined at 900°C for 3 h to obtain molybdenum carbide / seaweed carbon powder. 3 Polyvinyl alcohol powder dissolved in 66kg / m 3 In water, 0.6kg / m 3 Sodium alginate is dissolved in 16.5kg / m 3 Heat the water to 85°C and add 0.5kg / m 3 Defoamer, 3.6kg / m 3Molybdenum carbide / seaweed carbon powder was mixed and stirred for 65 seconds, and sodium hydroxide solution was added until the pH was > 12. After the solution was cooled, it was poured into a 300mm×300mm×6mm steel mold for curing. After demoulding, it was freeze-thawed for 3 times at -20℃ to obtain the wave-absorbing hydrogel. 3 、P·MH32.5 grade medium heat Portland cement 260kg / m 3 、Class I fly ash 63kg / m 3 , fine aggregate 740kg / m 3 , and add them into the mixer in sequence, stir evenly for 65 seconds to obtain mixture B. Add 2.2kg / m 3 , air entraining agent 0.04 kg / m 3 Mixing water 134kg / m 3 Evenly mix to obtain solution C. Slowly add solution C to mixture B within 15 seconds, slowly mix and stir for 50 seconds, pour the mixed slurry into a 300mm×300mm×60mm steel mold and pour 27mm, let it stand for 5 minutes, place the prepared absorbing hydrogel on the slurry, pour the remaining slurry, cure for 24 hours to form, and cure in a curing room for 28 days after demolding.
[0039] Comparative Example 1: The hydrogel-reinforced cement-based absorbing material of this embodiment, the upper layer of the absorbing material is a wave-transmitting layer, and the lower layer is a wave-absorbing layer, wherein the ratio of the raw materials of the wave-transmitting layer (kg / m 3 ) is: Portland cement 255, fly ash 63, dolomite coarse aggregate 1225, dolomite fine aggregate 740, high-efficiency water reducer 2.2, air entraining agent 0.04, water 134. The absorbing layer is molybdenum carbide / seaweed carbon powder, the material ratio (kg / m 3 ) is molybdenum carbide / seaweed carbon powder material 1.2.
[0040] The seaweed was washed three times with acetone, ethanol and pure water, and then dried in an oven for 12 hours. The dried seaweed was powdered, and the powder was dissolved in water with potassium hydroxide at a mass ratio of 1:2. After stirring for 6 hours, it was dried in an oven at 110°C, and then heated to 700°C in a tube furnace and pyrolyzed for 3 hours. 1 mol / L hydrochloric acid was added to the product until the pH was about 7, and seaweed carbon was obtained after drying. Take 12 kg / m 3 Seaweed carbon, 10kg / m 3 Molybdic acid, 110kg / m 3 Polyvinylpyrrolidone (PVP) is dissolved in 270kg / m 3 After stirring in methanol for 3 h, the mixed solution was placed in an oven at 110 °C and dried for 24 h. It was then placed in a tube furnace and calcined at 900 °C for 3 h to obtain molybdenum carbide / seaweed carbon powder. 3 、P·MH32.5 grade medium heat Portland cement 260kg / m3 、Class I fly ash 63kg / m 3 , fine aggregate 740kg / m 3 , 1.2kg / m 3 Molybdenum carbide / seaweed carbon powder were added into the mixer in turn and stirred evenly for 65 seconds to obtain mixture B. 3 , air entraining agent 0.04 kg / m 3 Mixing water 134 kg / m 3 Evenly mix to obtain solution C. Slowly add solution C into mixture B within 15 seconds, slowly stir and mix for 50 seconds, then pour the mixed slurry into a 300mm×300mm×60mm steel mold, cure for 24 hours to form, and cure in a curing room for 28 days after demoulding.
[0041] Comparative Example 2: The hydrogel-reinforced cement-based absorbing material of this embodiment, the upper and lower layers of the absorbing material are made of transparent layers, and the middle layer is made of absorbing hydrogel. The raw material ratio of the transparent layer (kg / m 3 ) is: Portland cement 255, fly ash 63, dolomite coarse aggregate 1225, dolomite fine aggregate 740, high-efficiency water reducer 2.2, air entraining agent 0.04, water 134. The absorbing hydrogel is polyvinyl alcohol hydrogel, and its dosage is based on the mass of the matching layer cement. The solid content of polyvinyl alcohol hydrogel is 9%. The absorbing layer is polyvinyl alcohol hydrogel, and the material ratio (kg / m 3 ) is polyvinyl alcohol 54.
[0042] 54kg / m 3 Polyvinyl alcohol powder dissolved in 66kg / m 3 In water, 0.6kg / m 3 Sodium alginate is dissolved in 16.5kg / m 3 Heat the water to 85°C and add 0.5kg / m 3 Defoamer, stir for 60s, add sodium hydroxide solution until pH>12, and after the solution is cooled, pour it into a 300mm×300mm×6mm steel mold for curing. After demoulding, freeze and thaw for 3 times at -20℃ to obtain polyvinyl alcohol hydrogel. 3 、P·MH32.5 grade medium heat Portland cement 260kg / m 3 、Class I fly ash 63kg / m 3 , fine aggregate 740kg / m 3 , and add them into the mixer in sequence, stir evenly for 65 seconds to obtain mixture A. Add 2.2kg / m 3 , air entraining agent 0.04 kg / m 3 Mixing water 134 kg / m 3Evenly mix to obtain solution B. Slowly add solution B to mixture A within 15 seconds, slowly mix and stir for 50 seconds, pour the mixed slurry into a 300mm×300mm×60mm steel mold and pour 27mm, let it stand for 5 minutes, place the prepared polyvinyl alcohol hydrogel on the slurry, pour the remaining slurry, cure for 24 hours to form, and cure in a curing room for 28 days after demolding.
[0043] Comparative Example 3: Raw material ratio of cement-based materials in this example (kg / m 3 ) is: Portland cement 255, fly ash 63, dolomite coarse aggregate 1225, dolomite fine aggregate 740, high-efficiency water reducer 2.2, air entraining agent 0.04, water 134.
[0044] Coarse aggregate 1225kg / m 3 、P·MH32.5 grade medium heat Portland cement 260kg / m 3 、Class I fly ash 63kg / m 3 , fine aggregate 740kg / m 3 , and add them into the mixer in sequence, stir evenly for 65 seconds to obtain mixture A. Add 2.2kg / m 3 , air entraining agent 0.04 kg / m 3 Mixing water 134 kg / m 3 Evenly mix to obtain solution B. Slowly add solution B into mixture A within 15 seconds, slowly stir and mix for 50 seconds, then pour the mixed slurry into a 300mm×300mm×60mm steel mold, cure for 24 hours, and cure in a curing room for 28 days after demoulding.
[0045] Comparative Example 4: The hydrogel-reinforced cement-based absorbing material of this embodiment, the upper and lower layers of the absorbing material are made of transparent layers, and the middle layer is made of absorbing hydrogel. The raw material ratio of the transparent layer (kg / m 3 ) is: Portland cement 255, fly ash 63, dolomite coarse aggregate 1225, dolomite fine aggregate 740, high-efficiency water reducer 2.2, air entraining agent 0.04, water 134. The raw material ratio of the wave-absorbing hydrogel (kg / m 3 ) is molybdenum carbide / seaweed carbon powder 7.2, polyvinyl alcohol 36.
[0046] The seaweed was washed three times with acetone, ethanol and pure water, and then dried in an oven for 12 hours. The dried seaweed was powdered, and the powder was dissolved in water with potassium hydroxide at a mass ratio of 1:2. After stirring for 6 hours, it was dried in an oven at 110°C, and then heated to 700°C in a tube furnace and pyrolyzed for 3 hours. 1 mol / L hydrochloric acid was added to the product until the pH was about 7, and seaweed carbon was obtained after drying. Take 12kg / m 3 Seaweed carbon, 10kg / m 3Molybdic acid, 110kg / m 3 Polyvinylpyrrolidone (PVP) is dissolved in 270kg / m 3 After stirring in methanol for 3 h, the mixed solution was placed in a 110°C oven and dried for 24 h. It was then placed in a tube furnace and calcined at 900°C for 3 h to obtain molybdenum carbide / seaweed carbon powder. 3 Polyvinyl alcohol powder dissolved in 66kg / m 3 In water, 0.6kg / m 3 Sodium alginate is dissolved in 16.5kg / m 3 Heat the water to 85°C and add 0.5kg / m 3 Defoamer, 7.2kg / m 3 Molybdenum carbide / seaweed carbon powder was mixed and stirred for 65 seconds, and sodium hydroxide solution was added until the pH was > 12. After the solution was cooled, it was poured into a 300mm×300mm×6mm steel mold for curing. After demoulding, it was freeze-thawed for 3 times at -20℃ to obtain the wave-absorbing hydrogel. 3 、P·MH32.5 grade medium heat Portland cement 260kg / m 3 、Class I fly ash 63kg / m 3 , fine aggregate 740kg / m 3 , and add them into the mixer in sequence, stir evenly for 65 seconds to obtain mixture B. Add 2.2kg / m 3 , air entraining agent 0.04 kg / m 3 Mixing water 134 kg / m 3 Evenly mix to obtain solution C. Slowly add solution C to mixture B within 15 seconds, slowly mix and stir for 50 seconds, pour the mixed slurry into a 300mm×300mm×60mm steel mold and pour 27mm, let it stand for 5 minutes, place the prepared absorbing hydrogel on the slurry, pour the remaining slurry, cure for 24 hours to form, and cure in a curing room for 28 days after demolding.
[0047] Comparative Example 5: The hydrogel-reinforced cement-based absorbing material of this embodiment, the upper and lower layers of the absorbing material are wave-transparent layers, and the middle layer is made of absorbing hydrogel. The raw material ratio of the cement wave-transparent layer (kg / m 3 ) is: Portland cement 255, fly ash 63, dolomite coarse aggregate 1225, dolomite fine aggregate 740, high-efficiency water reducer 2.2, air entraining agent 0.04, water 134. The raw material ratio of the wave-absorbing hydrogel (kg / m 3 ) is molybdenum carbide / seaweed carbon powder 3.0, polyvinyl alcohol 78.
[0048] The seaweed was washed three times with acetone, ethanol and pure water, and then dried in an oven for 12 hours. The dried seaweed was powdered, and the powder was dissolved in water with potassium hydroxide at a mass ratio of 1:2. After stirring for 6 hours, it was dried in an oven at 110°C, and then heated to 700°C in a tube furnace and pyrolyzed for 3 hours. 1 mol / L hydrochloric acid was added to the product until the pH was about 7, and seaweed carbon was obtained after drying. Take 12kg / m 3 Seaweed carbon, 10kg / m 3 Molybdic acid, 110kg / m 3 Polyvinylpyrrolidone (PVP) is dissolved in 270kg / m 3 After stirring in methanol for 3 h, the mixed solution was placed in a 110°C oven and dried for 24 h. It was then placed in a tube furnace and calcined at 900°C for 3 h to obtain molybdenum carbide / seaweed carbon powder. 3 Polyvinyl alcohol powder dissolved in 66kg / m 3 In water, 0.6kg / m 3 Sodium alginate is dissolved in 16.5kg / m 3 Heat the water to 85°C and add 0.5kg / m 3 Defoamer, 3kg / m 3 Molybdenum carbide / seaweed carbon powder was mixed and stirred for 65 seconds, and sodium hydroxide solution was added until the pH was > 12. After the solution was cooled, it was poured into a 300mm×300mm×6mm steel mold for curing. After demoulding, it was freeze-thawed for 3 times at -20℃ to obtain the wave-absorbing hydrogel. 3 、P·MH32.5 grade medium heat Portland cement 260kg / m 3 、Class I fly ash 63kg / m 3 , fine aggregate 740kg / m 3 , and add them into the mixer in sequence, stir evenly for 65 seconds to obtain mixture B. Add 2.2kg / m 3 , air entraining agent 0.04 kg / m 3 Mixing water 134 kg / m 3 Evenly mix to obtain solution C. Slowly add solution C to mixture B within 15 seconds, slowly mix and stir for 50 seconds, pour the mixed slurry into a 300mm×300mm×60mm steel mold and pour 27mm, let it stand for 5 minutes, place the prepared absorbing hydrogel on the slurry, pour the remaining slurry, cure for 24 hours to form, and cure in a curing room for 28 days after demolding.
[0049] Conclusion: The mechanical properties and absorbing properties of the absorbing materials prepared in Examples 1-3 and Comparative Examples 1-5 were tested, and the results were as follows: It can be seen from Examples 1-3 that the sandwich structure prepared by the seaweed carbon / molybdenum carbide powder and the polyvinyl alcohol hydrogel composition significantly improves the material's wave absorption performance and splitting tensile strength, and the different addition contents of seaweed carbon / molybdenum carbide powder have a significant effect on its electromagnetic wave absorption capacity. The seaweed carbon / molybdenum carbide powder has a high absorption capacity of 2.4-3.6 kg / m 3 Within the range, with the continuous increase of seaweed carbon / molybdenum carbide powder content, the compressive and splitting tensile strengths of the materials decreased, the cracking area increased significantly, and the reflection loss capacity showed a gradually increasing trend.
[0050] It can be seen from Comparative Examples 1-2 that, through the synergistic effect of polyvinyl alcohol hydrogel and seaweed carbon / molybdenum carbide powder, the reflection loss capacity, splitting tensile strength and crack resistance are better than those of single component materials.
[0051] As can be seen from comparative examples 3-5, as the content of seaweed carbon / molybdenum carbide powder and polyvinyl alcohol further increases, the reflection loss value of the material is greatly reduced. The principle is that seaweed carbon / molybdenum carbide powder belongs to a dual dielectric material, and its electromagnetic wave loss mechanism is mainly composed of its dielectric loss and conductive loss. When the content of seaweed carbon / molybdenum carbide powder is too high, clustering occurs, and its interconnection forms a conductive network to cause an electron tunneling effect to improve the conductivity of the material and cause material impedance mismatch, thereby reducing the material reflection loss ability. The synergistic effect of polyvinyl alcohol and seaweed carbon / molybdenum carbide powder not only improves the dispersion performance of seaweed carbon / molybdenum carbide powder, but also makes electromagnetic waves reflect multiple times inside the material, greatly increasing the reflection path of electromagnetic waves, and further improving the reflection loss ability of the material. The excellent water retention and high toughness of the hydrogel also significantly improve the splitting tensile performance and early crack resistance of concrete materials. Therefore, the hydrogel-enhanced cement-based absorbing material prepared by adding seaweed carbon / molybdenum carbide powder and polyvinyl alcohol hydrogel has good electromagnetic wave absorption ability and early crack resistance.
[0052] The above examples are only the preferred ratios for this test, and any adjustment of the component ratios within the scope of the present invention is within the scope of the present invention.
Claims
1. Hydrogel reinforced cement-based absorbing material, characterized in that The upper and lower layers are made of wave-transparent layers, and the middle layer is made of wave-absorbing hydrogel, among which: The wave-transmitting layer is composed of silicate cement, fly ash, water reducing agent, air entraining agent, and dolomite material, wherein: silicate cement 260-300 kg / m 3 , fly ash 80~100 kg / m 3 , water reducing agent 2~3 kg / m 3 , air entraining agent 0.08~0.16 kg / m 3 , water 110~140 kg / m 3 , dolomite material 1965~2267 kg / m 3 ; The wave-absorbing hydrogel is composed of molybdenum carbide / seaweed carbon powder, defoamer, sodium alginate, polyvinyl alcohol, and water, wherein: molybdenum carbide / seaweed carbon powder 2.4-3.6 kg / m 3 , defoamer 0.5~0.6 kg / m 3 , sodium alginate 0.6~0.7 kg / m 3 , polyvinyl alcohol 30~42kg / m 3 , water 66.4~76.4 kg / m 3 .
2. The hydrogel-reinforced cement-based absorbing material according to claim 1, characterized in that The silicate cement is P·MH32.5 grade medium heat silicate cement, with a fineness of less than 80μm and a specific surface area of ≥370kg / m 3 .
3. The hydrogel-reinforced cement-based absorbing material according to claim 1, characterized in that The fly ash is Class F, Grade I fly ash, with a fineness of <80μm.
4. The hydrogel-reinforced cement-based absorbing material according to claim 1, characterized in that The water reducer is a polycarboxylic acid high-efficiency water reducer with a solid content of ≥8.5%; the defoamer is an organosilicon defoamer with a viscosity of 160-200 MPa·s.
5. The hydrogel-reinforced cement-based absorbing material according to claim 1, characterized in that Dolomite includes coarse aggregate and fine aggregate, of which: coarse aggregate 1225~1413 kg / m 3 , fine aggregate 740~854 kg / m 3 .
6. The hydrogel-reinforced cement-based absorbing material according to claim 1, characterized in that The particle size of molybdenum carbide / seaweed carbon powder is 120-180μm, and the specific surface area is ≥250m 3 / g; wherein the particle size of molybdenum carbide particles is 50-80nm.
7. A method for preparing a hydrogel-reinforced cement-based wave absorbing material, characterized in that The following steps are involved: S1, the seaweed was washed three times with acetone, ethanol and pure water, and then dried in an oven for 12 h. The dried seaweed was made into seaweed powder. The seaweed powder and potassium hydroxide were dissolved in water at a mass ratio of 1:2, stirred for 5-8 h to mix evenly, and then dried in an oven at 100-110 °C. After the dried sample was fully ground, it was heated in a N2 environment at a heating rate of 2-3 °C / min. After heating to 600-800 °C, it was activated and pyrolyzed for 2-3 h. 1 mol / L hydrochloric acid was added dropwise to the product until the pH was 7±0.5, and then centrifuged, washed and dried to obtain seaweed carbon. S2, take 10kg / m 3 Molybdic acid, 110kg / m 3 Polyvinylpyrrolidone (PVP) is dissolved in 270kg / m 3 Stir in methanol for 2-3 h, then add 12 kg / m 3 The seaweed carbon prepared in step S1 is stirred for 1-2 hours and then ultrasonicated for 30-60 minutes to make it uniformly dispersed, and the mixed solution is placed in an oven at 100-110°C and dried for 24 hours; The dried black powder is placed in a tube furnace and calcined at 800-1000°C for 2-3 hours to obtain molybdenum carbide / seaweed carbon powder; S3, 30~42kg / m 3 kg / m 3 Polyvinyl alcohol is dissolved in 66.4kg / m 3 In water, 0.6~0.7kg / m 3 Sodium alginate dissolved in 10kg / m 3 Heat the water to 80~90℃ and add 0.5~0.6kg / m 3 Defoamer, 2.4~3.6 kg / m 3 The molybdenum carbide / seaweed carbon powder prepared in step S2 is mixed and stirred for 50-70 seconds, and a sodium hydroxide solution is added dropwise until the pH value is greater than 12. After the solution is cooled, it is poured into a steel mold for curing to a thickness of 1-6 mm. After demolding, it is freeze-thawed at -20°C for 3-15 times to obtain a microwave absorbing hydrogel; S4, 1965~2267 kg / m 3 Dolomite, 260~300 kg / m 3 Portland cement and 80~100 kg / m 3 Add fly ash into the mixer and stir evenly for 60-80 seconds to obtain wave-transmitting layer powder; S5, add 2~3 kg / m 3 , air entraining agent 0.08~0.16 kg / m 3 110~140 kg / m 3 The water is mixed evenly to obtain a wave-transmitting layer mixed solution; S6, start the stirrer, slowly add the mixed solution prepared in step S5 into the wave-transmitting layer powder prepared in step S4 within 15 seconds, and stir slowly for 35 to 60 seconds to obtain a wave-transmitting layer mixed slurry; S7, pour the wave-transmitting layer mixed slurry prepared in step S6 into a 300mm×300mm×60mm steel mold and cast 24~27mm, let it stand for 5~30min, then place the absorbing hydrogel on the wave-transmitting layer mixed slurry, then cast the remaining wave-transmitting layer mixed slurry, and cure for 24h to form it. After demolding, cure it in a curing room for 28 days to obtain a hydrogel reinforced cement-based absorbing material.